1976
DOI: 10.1002/1097-0142(197604)37:4<1977::aid-cncr2820370450>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral pulmonary carcinoid tumors

Abstract: The light microscopic and ultrastructural features of five asymptomatic peripheral carcinoids presented as distinct pulmonary solitary nodules are described. By conventional microscopy the tumors displayed a variety of histologic patterns, the most unusual one showing tumor cells embedded in a richly vascular hyalinized stroma and forming papillary structures or cystic spaces lined by low cuboidal cells which ultrastructurally bore a strong resemblance to intermediate or transitional forms between types I and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0
4

Year Published

1976
1976
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 50 publications
3
19
0
4
Order By: Relevance
“…It is of interest that the clearly defined subgroup of peripheral tumours documented by Salyer et al (1975) was characterised by spindle cell composition, anisocytosis, anisonucleosis, and overall disorganization of structure. Our finding of peripheral tumours which generally resembled their central counterparts is consonant with the work of other authors (Felton et al, 1953;Bonikos et al, 1976). It is possible that the unmixed pattern seen in three of the peripheral lesions may have been related to size as two of the tumours were less than 1 cm diameter.…”
Section: Discussionsupporting
confidence: 92%
“…It is of interest that the clearly defined subgroup of peripheral tumours documented by Salyer et al (1975) was characterised by spindle cell composition, anisocytosis, anisonucleosis, and overall disorganization of structure. Our finding of peripheral tumours which generally resembled their central counterparts is consonant with the work of other authors (Felton et al, 1953;Bonikos et al, 1976). It is possible that the unmixed pattern seen in three of the peripheral lesions may have been related to size as two of the tumours were less than 1 cm diameter.…”
Section: Discussionsupporting
confidence: 92%
“…Although various histological types of lung tumors have been produced experimentally with Et2NNO (1,44), lung endocrine-like cells or their progenitors may be particularly sensitive to its carcinogenic effects (45). Taken together, the hyperplastic and progressive changes observed in NEBs in the present study may recapitulate the histopathological events occurring in the formation of peripheral pulmonary carcinoids (46) and bronchial carcinoid tumors and the progression to less differentiated lung carcinomas, such as small-cell carcinomas, which exhibit few cells with APUD characteristics. However, the relationship between the cellular alterations of the NEB cell population and tumor induction with Et2NNO in various segments of the airways of hamsters is as yet uncertain.…”
supporting
confidence: 74%
“…The presence of a glandular or tubular pattern in the tumours is well recognised (Weiss and Ingram, 1961;Fu et al, 1974), and in a number of cases simple and complex gland lumina with bordering microvilli have been demonstrated on electron microscopy (Fu et al, 1974;Bell et al, 1975;Sonksen et al, 1976). More frequently, ultrastructural study of bronchial carcinoid tumours has revealed the presence of intercellular canaliculi with projecting microvilli (Elliott and Hardy, 1971;Renault and Verley, 1973;Patchefsky et al, 1974;Bell et al, 1975;Bonikos et al, 1976).…”
mentioning
confidence: 99%